Young, gifted and lazy? The role of ability and labor market prospects in student effort decisions - Adrian Chadi; Marco De Pinto; Gabriel Schultze (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2017)
This paper examines the decision-making process of students from an economic perspective in order to understand what determines an individual's willingness to provide effort. Our theoretical model predicts that ability and job market prospects are positive determinants. Analyzing a novel dataset on thousands of German students, however, we instead find that ability has a significantly negative effect on effort. It seems that the marginal gain of increasing effort in terms of higher expected income after studying is lower for high-ability students compared to low-ability students. In regard to the second determinant, the evidence rejects a similar argument, according to which great job market prospects may impair student effort. Applying an instrumental variable approach based on official unemployment data on regional labor markets, we can confirm our prediction on the positive role of perceived employment prospects in actual student behavior.
Keywords: I23; J22; J24; 330; higher education; effort; study time; leisure; ability; labor market data